2010
DOI: 10.1248/bpb.33.1082
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/Pharmacodynamic Modeling and Simulation of Rosuvastatin Using an Extension of the Indirect Response Model by Incorporating a Circadian Rhythm

Abstract: In 2004, the United States Food and Drug Administration issued a "critical path" document for characterizing modelbased drug development as the development and application of pharmacostatistical models of drug efficacy and safety from preclinical and clinical data to improve drug development knowledge management and decision making.1,2) Pharmacokinetic/pharmacodynamic (PK/PD) modeling and simulation also enable the prediction of the effects of a medicine in various situations in clinical practice. The effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…The simulated reduction in MVA AUC relative to baseline of 34 and 27%, respectively, for the evening and morning dose of rosuvastatin is in reasonable agreement with the reduction of 40 and 32% simulated by Aoyama et al 21 using their PK/PD model with plasma concentration as the PD model input. The study used in fitting of the model 7 is the only published clinical study that has reported the change in plasma MVA concentration after rosuvastatin administration.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The simulated reduction in MVA AUC relative to baseline of 34 and 27%, respectively, for the evening and morning dose of rosuvastatin is in reasonable agreement with the reduction of 40 and 32% simulated by Aoyama et al 21 using their PK/PD model with plasma concentration as the PD model input. The study used in fitting of the model 7 is the only published clinical study that has reported the change in plasma MVA concentration after rosuvastatin administration.…”
Section: Discussionsupporting
confidence: 85%
“…The liver Cu IW AUC 0–∞ was reduced by 5.7 and 9.6%, respectively ( Table 1 ). The average MVA AUC relative to baseline corresponding to these sequence variations was increased by 30 and 35% when plasma concentration was used as the input to the PD response model, as in the original model 21 ( Table 1 ). However, when liver Cu IW was used as the input to the PD response in our modified model, the simulated average MVA AUC relative to baseline was reduced by 3.1 and 5.8%, respectively ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations